Trust, privacy, community, and culture: Important elements of maternity care for Aboriginal and Torres Strait Islander women giving birth in Victoria. Issue 1 (February 2023) - McCalman, P.; McLardie-Hore, F.; Newton, M.; McLachlan, H.; Forster, D.
Abstract: Background: The Australian maternity system must enhance its capacity to meet the needs of Aboriginal and Torres Strait Islander (First Nations) mothers and babies, however evidence regarding what is important to women is limited. Aims: The aim of this study was to explore what women having a First Nations baby rate as important for their maternity care as well as what life stressors they may be experiencing. Methods: Women having a First Nations baby who booked for care at one of three urban Victorian maternity services were invited to complete a questionnaire. Results: 343 women from 76 different language groups across Australia. Almost one third of women reported high levels of psychological distress, mental illness and/or were dealing with serious illness or death of relatives or friends. Almost one quarter reported three or more coinciding life stressors. Factors rated as most important were privacy and confidentiality (98 %), feeling that staff were trustworthy (97 %), unrestricted access to support people during pregnancy appointments, (87 %) birth (66 %) and postnatally (75 %), midwife home visits (78 %), female carers (66 %), culturally appropriate artwork, brochures (68 %) and access to Elders (65 %). Conclusions: This study provides important information about what matters to women who are having a First Nations baby in Victoria, Australia, bringing to the forefront social and cultural complexities experienced by many women that need to be considered in programme planning. It is paramount that maternity services partner with First Nations communities to implement culturally secure programmes that respond to the needs of local communities.